Existence and Uniqueness of Periodic Solutions for a Second-Order Nonlinear Differential Equation with Piecewise Constant Argument - Gen-qiang Wang; Sui Sun Cheng (International Journal of Mathematics and Mathematical Sciences)
Based on a continuation theorem of Mawhin, a unique periodic solution is found for a second-order nonlinear differential equation with piecewise constant argument.